(untitled) (Biological Sciences - PJSIR, 2006)
Six esters were synthesized from their parent acids, while their corresponding hydrazides were subsequently synthesized from these esters. The hydrazides, on reaction with benzaldehyde, produced their respective hydrazones, namely, benzoic hydrazone (BH), m-nitrobenzoic hydrazone (m-NBH), p-nitrobenzoic hydrazone (p-NBH), 3,5- dinitrobenzoic hydrazone (3,5-DNBH), m-aminobenzoic hydrazone (m-ABH), and p-aminobenzoic hydrazone (p-ABH). These hydrazones, on interaction with magnesium chloride yielded their corresponding magnesium com- plexes. These complexes were off-white, grey or brownish in colour. These complexes were characterized on the basis of spectral data and metal analysis. Metal to ligand stoichiometry of 1 : 3/2 and 1 : 5/2 has been proposed for the complexes. The relevant infrared bands in the ligands and complexes were used to assign the probable point(s) of coordination.